The biographies of the Dalai Lamas - Ya, Hanzhang (Foreign Languages Press Distributed by China International Book Trading Corp, 1991)
With special emphasis on the times of Thub-bstan-rgya-mtsho, Dalai Lama XIII, 1876-1933 and his political role in Tibet